Mucinous Tubular and Spindle Cell Carcinoma of the Kidney: A Case Series of Three Patients Including Rare Presentations and Histological Variants - Vaishali Rohilla; Deepak Kumar Garg; Maneesh Kumar Vijay; Vishal Rohilla; Anshul Rohilla, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Mucinous Tubular and Spindle Cell Carcinoma (MTSCC) is a rare subtype of renal cell carcinoma (RCC), typically characterized by a biphasic pattern of tubules and spindle cells embedded in a mucinous stroma. It presents diagnostic challenges due to overlapping features with other RCC subtypes. Most cases are detected incidentally. Objective: To describe the clinicopathological characteristics and diagnostic challenges of MTSCC through a series of three cases with varying presentations and histological features. Case Presentation: Case 1: A 59-year-old male presented with non-specific abdominal pain and chronic constipation. Imaging revealed an exophytic lesion in the left kidney. Partial nephrectomy and histopathology confirmed MTSCC with low-grade features and focal capsular invasion. Case 2: A 47-year-old female presented with intermittent hematuria and flank pain. Imaging detected a well-circumscribed lesion in the lower pole of the left kidney. Radical nephrectomy was performed. Histology showed MTSCC with epithelial predominance and oncocytic changes. Case 3: A 64-year-old asymptomatic postmenopausal female was evaluated for uterine bleeding. Incidental renal mass was found on MRI. Partial nephrectomy revealed classic MTSCC with focal high-grade transformation, characterized by increased mitoses and nuclear atypia. Results: All cases demonstrated classic biphasic histomorphology. Immunohistochemistry showed CK7 and PAX8 positivity and CD10 negativity in all three cases. The Ki-67 index ranged from <5% in low-grade tumors to ~20% in areas of high-grade transformation. No metastases were detected, and all patients were placed on surveillance. Conclusion: MTSCC is an indolent renal tumor with distinct histological and immunohistochemical features. Although typically low-grade, some tumors may exhibit aggressive behavior, underscoring the importance of accurate histopathological evaluation. Close follow-up is recommended due to the potential for high-grade transformation and recurrence.